2019
DOI: 10.1161/circgen.118.002384
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics, Atrial Conduction, and Body Mass Index

Abstract: Background: Lipids are increasingly involved in cardiovascular risk prediction as potential proarrhythmic influencers. However, knowledge is limited about the specific mechanisms connecting lipid alterations with atrial conduction. Methods: To shed light on this issue, we conducted a broad assessment of 151 sphingo- and phospholipids, measured using mass spectrometry, for association with atrial conduction, measured by P wave duration (PWD) from standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This result is consistent with previous data reporting altered lipid metabolites and, in particular, a minor amount of lysoPC a C20:3 in AF patients [ 11 ]. Moreover, in a recent analysis [ 48 ] conducted in a related population-based study from the same region, we observed an association between higher levels of another phosphatydilcholine, the PC38:3, and longer P wave duration, which is also a risk factor for AF [ 49 ]. Even though the association was replicated in an independent population sample from Scotland, proving its robustness, mediation and Mendelian randomization analyses showed that the association between PC38:3 and P wave was caused by the confounding role of BMI: in fact, BMI was proven to cause both PC38:3 increase and P wave prolongation [ 48 ].…”
Section: Discussionmentioning
confidence: 96%
“…This result is consistent with previous data reporting altered lipid metabolites and, in particular, a minor amount of lysoPC a C20:3 in AF patients [ 11 ]. Moreover, in a recent analysis [ 48 ] conducted in a related population-based study from the same region, we observed an association between higher levels of another phosphatydilcholine, the PC38:3, and longer P wave duration, which is also a risk factor for AF [ 49 ]. Even though the association was replicated in an independent population sample from Scotland, proving its robustness, mediation and Mendelian randomization analyses showed that the association between PC38:3 and P wave was caused by the confounding role of BMI: in fact, BMI was proven to cause both PC38:3 increase and P wave prolongation [ 48 ].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the minimal volume of the sample collected onto VAMS enables longitudinal metabolomic studies and is particularly in line with the 3R’s principle [ 14 ]. The integration of VAMS with conventional mass spectrometry (MS)-based metabolomics approaches is an attractive solution for different applications, ranging from animal studies to human population studies [ 27 , 28 ] and longitudinal studies [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Techniques of lipidomics have been applied in some clinical studies for assessing the association of AF. One study found that BMI-correlated increased PC 38:3 was associated with atrial conduction, which was represented by P wave duration 61 . Another study found that AF patients had different fatty acids and phospholipids in the plasma than healthy controls 62 .…”
Section: Discussionmentioning
confidence: 99%